Growing Up in Australia takes its first steps - Sanson, A; FaHCSIA LSAC Project Team; Johnstone, R; LSAC Research Consortium (My University, 2004)
Growing Up in Australia is the longitudinal study of Australian children. It is a large scale and complex study, focusing on children's health, social and emotional development, early child care and educational experiences, family lives and community interactions. The study aims to provide a strong evidence base for policy and practice. This article describes the study's development process, discusses the data that will be available to researchers from the first wave of data collection, and offers some pointers to the sorts of questions that can be addressed using the Growing Up in Australia dataset.
Keywords: Surveys and Survey Methodology; Surveys and Survey Methodology; Surveys and survey methodology; Surveys and Survey Methodology; Surveys and Survey Methodology